52.8k views
5 votes
If 5a=-4b+5 and 3a=-2b+3, what is 6b?

User Ateiob
by
6.0k points

1 Answer

1 vote
There are two equations and two variables. You can solve for each variable using either the elimination method or the substitution method. Here, I believe the elimination method would be best:
5a = -4b + 5
3a = -2b + 3
You can multiply the second equation by two, so the 4b and -4b in both equations will cancel each other out when you add them. So:
5a = -4b +5
6a = 4b +6
Add both equations together.
11a = 11
a = 1
Plug in the a value into any of the previous equations:
5(1) = -4b + 5
-4b = 0
b = 0
So, since we know that b = 0, 6b is also 0.
User William Hu
by
5.4k points